A novel exo-lytic and disaccharide-yielding glycosaminoglycan lyase from a marine-derived polysaccharide-degrading actinobacterium Microbacterium sp. strain WS15 - Li, Peng; Ma, Zaichao; Zou, Ruyi; Gu, Jingyan; Shan, Ningning; Han, Wenjun; Wang, Hailong; Li, Fuchuan; Tan, Haining (Frontiers in Microbiology, 2025)
IntroductionGlycosaminoglycan (GAG) lyases play key roles in preparing oligosaccharides, treating human diseases, and learning relationships between complex structures and various functions of carbohydrates. An endo-lytic enzyme will depolymerize GAGs randomly and finally produce a series of size-defined oligosaccharide fractions, whereas an exo-lytic lyase can usually yield the sole final oligosaccharide products. However, it is difficult to distinguish them directly depending on protein sequences, which limits further resource exploration.Results and DicussionIn this study, we initially isolated and identified a marine-derived polysaccharide-degrading actinobacterium, Microbacterium sp. strain WS15, and subsequently explored by genome sequencing and data mining, as a new candidate GAGs lyase within the eighth polysaccharide lyase (PL8) family, sharing high sequence identity with characterized endo-type GAG lyases. The recombinant proteins of TT16 were optimal at 50 °C and pH 7.0, respectively, and active against multiple polysaccharide substrates, including both unsulfated GAG (e.g., hyaluronate) and sulfated GAGs (e.g., chondroitin sulfate A–E types), implying a broad spectrum based on sulfation tolerance. However, TT16 was novel for predominantly yielding unsaturated disaccharides as an exo-type lyase, rather than an endo-type lyase, with the smallest substrate being associated with tetrasaccharides, suggesting the potential in disaccharide preparation. Comparative enzymatic analyses indicated that all the biochemical characteristics and catalytic properties were determined by the TT16 protein rather than the additional protein tag. Moreover, protein structure modeling followed by molecular docking revealed that protein TT16 showed low binding energies with various donors, and its catalytic cavity was large and flexible to accommodate either two unsulfated hyaluronate disaccharides or a chondroitin sulfate E (CSE) tetrasaccharide with four sulfate groups as a donor, implying a structural basis suitable for the disaccharide-yielding type. Furthermore, the motif of Tyr284, Asn225, and His275 also provided the catalytic basis for β-elimination, while residues Ala71 and Arg219 might be essential for the novel exo-lytic mode.SignificanceThis study provided the protein TT16 as a novel exo-lytic tool for preparing unsaturated GAG disaccharides and the potential exo-lytic mechanism, which will benefit the initial enzyme identification and further property improvements